Damping characteristic identification and damage assessment of a three-storey aluminium frame - Akhila, T.S.; Saji, K.P. (Journal of Structural Engineering, 2024)
Monitoring of the large structural systems for purposes of assessing the potential degradation of structural propertiesby identifying the dynamic characteristics is needed for assuring the safety of the system. Measurements made ata single point in the structure can be used to detect, locate and quantify the damage. In this work, a method fordetermining the damping characteristics and identifying the presence, location and severity of structural damage byobserving the potential degradation of modal characteristics is presented. This method uses the dynamic propertiesobtained from the vibration response of the structure both in damaged and undamaged conditions. A three-storiedaluminium base frame and 8 damage induced frames were experimentally studied by horizontal shake table. Thedamage was induced in the base frame by reducing the cross-section of the column. The experimental observations interms of frequency, displacement and acceleration were used to obtain the dynamic characteristics of the structure. Bycomparing both theoretical and experimental results of the storey level deflection, the damping ratio of the structure isidentified. The identified damping ratio corresponding to each frame is used in the damage assessment algorithm. Thisalgorithm gives reduced storey level stiffness of the structure. The characteristics of the damage in 8 damage inducedframes are identified from the results. The method is verified by comparing obtained reduced stiffness with manuallycalculated stiffness value. The reduction in the stiffness of each storey reflects the location of the damaged column. Theanalytical results show that the presented method can lead to satisfactory results in most cases.